Using digital layers to evoke nostalgia in hybrid gifting - Gibson, Rebecca (2024)
We accumulate vast physical and digital possessions throughout our lives, making it difficult to organise, share, and reflect on amassed repositories. The increased availability of capture has resulted in some deliberately capturing media with the aim to one day reflect and feel nostalgic. Nostalgia involves a range of bittersweet emotions including joy, loneliness, and regret. Yet, it remained unclear if and how nostalgic media could potentially be repurposed or re-framed as a gift. Gifting is a social ritual and typically involves the transfer of a physical gift item or product. An emerging modality of gifting entitled ‘Hybrid Gifting’ is defined as blending physical and digital objects to create a single gift. This thesis focuses on hybrid gifting but with a specific angle to explore nostalgia. Despite thematic links of social bonds, communication, and relationships there remained a notably absent research gap in bringing together the areas of gifting, technologies, and emotions. The primary aim of this thesis was to explore if a hybrid gifting modality could facilitate nostalgic experiences and uncover the unique perspectives of those involved in a gift exchange: gift-givers, gift-recipients, and gift-producers. This research took a multidisciplinary approach and was underpinned by areas of marketing, consumer research, psychology, anthropology, and human-computer in- teraction. A range of qualitative methods were adopted to explore the research aims and perspectives: interviews, focus groups, technology probes, and reflexive thematic analysis. This thesis is made up of four main studies and is the first to combine embedding nostalgic emotions within a hybrid gifting modality. The first study entitled ‘The Memory Machine’ explores the concept of transforming media and memories into a digital gift from a gift-giver perspective. The second study entitled ‘The Nostalgic Gifting Study’ aimed to understand how a hybrid gift could help facilitate nostalgic experiences and the implications of trying to evoke nostalgia through personal digital media for both gift-giver and receiver. The third study entitled ‘The Tailored Gifting Study’ aimed to explore: “Can physical and digital objects combine to create a nostalgic narrative? And if so, how does this happen in a hybrid gift exchange?” Lastly, the fourth study entitled ‘The Gift Producer Study’ aimed to understand gift producer opinions on the potential challenges and opportunities of creating hybrid gift products. The contributions of this work are both theoretical and practical. Firstly, the theoretical contributions relate to four unique areas: (1) Bittersweet nostalgia facilitated by hybrid gift exchange: which involves a definition of nostalgic hybrid gifts, an understanding of how nostalgic emotions can be evoked in hybrid gift exchanges, and any impacts of this. (2) The role of objects in hybrid gift exchanges: which involves a unique understanding of physical objects in hybrid exchanges and the affordances of blending physical and digital objects in an exchange: a memorable exchange, psychological benefits, ongoing connections, and multi-sensory presentation. (3) Technologies and hybrid gift: which outlines specific knowledge on the use of QR codes in hybrid gift exchanges, gift producer views on technologies for hybrid product design, and how technologies enable communication via hybrid modality. (4) Meaningful relationships: which highlights the types of motivations gift-givers have for gifting a memory, the roles of the gift-giver, recipient, and producer, and the impact on relationships of sending/receiving a hybrid gift. Moreover, there are three practical design implications of this work. Firstly, ‘rituals and technologies’ suggests a considered use of technology to enhance social rituals and highlights the importance of balancing tradition and evolution when designing in the rituals space. Secondly, ‘blended experiences and emotional possibilities’ encourages contemplation of aesthetic design, layering of media, and the emotional possibilities when physical and digital objects are matched. Finally, ‘designing with nostalgia’ outlines the subjective challenges of designing with or for nostalgia but also how themes, prompts, and inspiration can be used to guide consumers/participants to create nostalgic narratives.